PENGARUH GAYA KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI KECAMATAN DI PAMEKASAN - Mohammad Hamzah (Cahaya Ilmu Bangsa, 2024)
Leadership has a central role in organizational and group life. To achieve common goals, people in an organization need to build togetherness by following the control of their leader. With this control, differences in desires, wills, wishes, feelings, needs and so on are brought together to be moved in the same direction. This means that in every organization individual differences are utilized to achieve the same goals as leadership activities. A leader is a person who leads or influences other people in a company or organization. Organizational culture is a characteristic that exists in a group and is used as a guide for their behavior and differentiates them from other groups. Or organizational culture is a set of behavioral norms and values that must be understood and obeyed by the group of people who adhere to it. So, this will have an impact on the performance of employees in an organization or company